Cardiac tamponade occurred after endoscopic submucosal dissection: conservative management of the esophagopericardial fistula. Issue 12 (20th October 2017) - Bona, Davide; Saino, Greta Isabella; Medda, Massimo; Panizzo, Valerio; Micheletto, Giancarlo
Key Clinical Message: We describe the case of an esophagopericardial fistula generated after endoscopic submucosal dissection in a patient affected by a superficial esophageal squamous cell carcinoma immediately treated with percutaneous pericardial drainage and placement of a partially covered self‐expanding metal stent that has been removed using the stent‐in‐stent technique after 35 days. Abstract : We describe the case of an esophagopericardial fistula generated after endoscopic submucosal dissection in a patient affected by a superficial esophageal squamous cell carcinoma immediately treated with percutaneous pericardial drainage and placement of a partially covered self‐expanding metal stent that has been removed using the stent‐in‐stent technique after 35 days.